Management Strategy for Optimizing the Role of Guru Penggerak at SMAN 1 Sawahlunto - Arnol, Arnol; Siskawati, Oies Febria; Rusmita, Rusmita; Fazis, Muhammad; Christoph, Nash (al-fikrah: Jurnal Manajemen Pendidikan, 2024)
This study outlines a strategic management approach to optimize the role of Guru Penggerak (Mobilizing Teachers) in enhancing education quality at SMAN 1 Sawahlunto, Indonesia. The study employs an exploratory qualitative methodology, incorporating data collection through interviews, documentation studies, and observations. Using SWOT analysis, the study examines internal and external factors influencing the implementation of Guru Penggerak programs. The findings reveal that leveraging Guru Penggerak strengthens school culture, fosters differentiated learning and develops superior student profiles. The novelty lies in its detailed framework for maximizing teacher contributions under the Independent Learning Program. This research contributes to educational transformation by offering actionable strategies for principals and policymakers to optimize teacher leadership, collaboration, and innovation.